From office tools to community supports: The need for infrastructure to address the social determinants of health in paediatric practice. Issue 4 (1st April 2014) - Fazalullasha, Fatima; Taras, Jillian; Morinis, Julia; Levin, Leo; Karmali, Karima; Neilson, Barbara; Muskat, Barbara; Bloch, Gary; Chan, Kevin; McDonald, Maureen; Makin, Sue; Ford-Jones, E Lee
Abstract: Previous research has highlighted the importance of addressing the social determinants of health to improve child health outcomes. However, significant barriers exist that limit the paediatrician's ability to properly address these issues. Barriers include a lack of clinical time, resources, training and education with regard to the social determinants of health; awareness of community resources; and case-management capacity. General practice recommendations to help the health care provider link patients to the community are insufficient. The objective of the current article was to present options for improving the link between the office and the community, using screening questions incorporating physician-based tools that link community resources. Simple interventions, such as routine referral to early-year centres and selected referral to public health home-visiting programs, may help to address populations with the greatest needs.